PERAN SELF-BRAND CONNECTION DALAM MEMEDIASI PENGARUH KREDIBILITAS ENDORSER TERHADAP BRAND EQUITY PADA BRAND GUESS - Widyajayanti, Ni Putu Maha Dewi; Kusuma, A.A Gede Agung Artha (E-Jurnal Manajemen; Vol 6 No 6 (2017), 2017)
The emergence of the intense competition in the field of fashion business requires marketers to be more careful and creative in marketing their products. This study was conducted to clarify the effect of endorser credibility to self-brand connection and brand equity, the effect of self-brand connection to the brand equity, and the role of self-brand connection in mediating the effect of endorser credibility to the brand equity. This research was conducted in Badung with a sample size of 120 respondents using purposive sampling and accidental sampling. The collection of data obtained from the results of questionnaires using a five-point Likert scale used to measure 12 indicators using Path analysis and Sobel test. The results showed that the credibility of the endorser and self-brand connection significantly positive effect on brand equity, self-brand connection is of significance is able to mediate the relationship between the credibility of the endorser of the brand equity. These results indicate that self-brand connection an important role in how the credibility of an endorser who will have an impact on brand equity.
Keywords: endorser credibility, self-brand connection, brand equity